Association of urinary bisphenol A levels with heart failure risk in U.S. adults from the NHANES (2003–2016) - Ma, Yuanyuan; Huang, Haobin; Qian, Haiyun; Wu, Yanhu; Gao, Zhe (Frontiers in Cardiovascular Medicine, 2024)
Introduction Although heart failure (HF) has been linked to bisphenol A (BPA), few studies have investigated the cut-off values for the effects of urinary BPA levels on heart failure risk. The association between urinary BPA levels and HF prognosis has not been investigated. Methods This study included 11,849 adults over 20 years old using information from the National Health and Nutrition Examination Survey (NHANES), which was conducted from 2003 to 2016. The relationship between urinary BPA levels and the risk of HF was determined via a multivariable logistic regression model, and restricted cubic spline (RCS) methods were used to determine the cut-off for the effect of BPA levels on HF risk. Based on the available NT-proBNP concentration data from the NHANES (2003–2004), multivariable linear regression was applied to determine the linear association between the NT-proBNP concentration and urinary BPA concentration. Results The results revealed a positive correlation between a urinary BPA concentration in the fourth quartile and the occurrence of heart failure [OR 1.49, 95% CI (1.09, 2.04), p = 0.012]. A one-unit increase (1 ng/mg creatinine) in the ln-transformed BPA concentration was linked to a 15% increase in the incidence of HF [OR 1.15, 95% CI (1.03, 1.29), p = 0.014]. The cut-off urinary BPA concentration for HF risk was 1.51 ng/mg creatinine. There was a positive correlation between urinary BPA and NT-proBNP concentrations [β = 0.093, 95% CI (0.014, 0.171), p = 0.02] in males, but there was no linear association [β = 0.040, 95% CI (−0.033, 0.113), p = 0.283] in females. Discussion Increased urinary BPA levels are linked to an increased risk of heart failure and poor prognosis. There is a significant increase in the risk of heart failure if the urinary concentration of BPA exceeds 1.51 ng/mg creatinine.